Aposentadoria e êxodo rural no município de Nova Boa Vista- RS: o caso dos aposentados que migram para a cidade - Schumacher, Jacson Dreyer (2019)
The present research deals with a study about rural retirement and rural exodus in the municipality of Nova Boa Vista / RS, and in this municipality it is common to occur the process of migration of the rural population to the city after obtaining rural retirement. In this scenario of migration from the countryside to the city, the present investigation seeks to answer the following question: because the rural inhabitants migrate to the city of Nova Boa Vista / RS after obtaining the rural retirement. To answer the research problem, it was established as a general objective: To understand the process of rural-urban migration by the elderly population after obtaining the rural retirement in the municipality of Nova Boa Vista - RS. Specifically, it is intended to: Identify the reasons that lead retirees to leave the rural area and migrate to the city, after the achievement of retirement. Understand the role of retirement as a driver of the process of migration to the city. To verify the trajectory of the retired ones as residents of the field as well as the determining factors in the migration to the city. Understand the routine of retirees as residents of the city and check what attractions offered by the city. In order to reach the objectives proposed in the present research, we opted for the use of the approach and the qualitative analysis. The selected method, which is closest to the reality of the research, was the dialectic. For better organization and understanding, this work is presented methodologically divided into three stages. The first stage consisted of the initial and constant orientations, survey and analysis of the bibliographic material, constituting the basis for the construction of the theoretical reference of the research. The second stage is composed by the collection of primary data, carried out through fieldwork, together with the retirees who migrated from the countryside to the city of Nova Boa Vista / RS after obtaining the rural retirement. At first, the characterization of the municipality was carried out, taking into account the cultural, social and economic characteristics among other aspects, after which the data collection was carried out with the retirees through semi-structured interviews, informal conversations and observations. The third phase consists of the crossing of data and information collected, making possible a specific analysis of the study area. In the city of Nova Boa Vista / RS there is a significant number of retirees who migrated from the countryside to the city after obtaining rural retirement. The retirees of this municipality point to the innumerable changes that the field has presented over the years, and this is not in their perspectives a place to live the old age, highlighting the exacerbated use of pesticides, lack of leisure among other issues. In this municipality there is historically a concern to maintain a good quality of life for the elderly population of the municipality, since the public policies focused on this part of the population are diverse.